2013
DOI: 10.1098/rspb.2012.2484
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of individual birds in starling flocks

Abstract: Flocking is a paradigmatic example of collective animal behaviour, where global order emerges out of self-organization. Each individual has a tendency to align its flight direction with those of neighbours, and such a simple form of interaction produces a state of collective motion of the group. When compared with other cases of collective ordering, a crucial feature of animal groups is that the interaction network is not fixed in time, as each individual moves and continuously changes its neighbours. The poss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(134 citation statements)
references
References 36 publications
8
126
0
Order By: Relevance
“…Computations and inference of effective interactions can be in this case much more complicated. For polarized self-propelled systems we showed that, as long as the network of positions does not rearrange too fast (which is the case of natural flocks [51]), static and dynamic ME models give a very similar inference of the interaction parameters [40].…”
Section: Maximum Entropy Approach To Flocksmentioning
confidence: 91%
“…Computations and inference of effective interactions can be in this case much more complicated. For polarized self-propelled systems we showed that, as long as the network of positions does not rearrange too fast (which is the case of natural flocks [51]), static and dynamic ME models give a very similar inference of the interaction parameters [40].…”
Section: Maximum Entropy Approach To Flocksmentioning
confidence: 91%
“…This is not the case for starlings. In this respect, in contrast, flocks are rather structureless systems, with individuals continuously exchanging positions [33] and with a distribution of mutual distances lacking any structure. A good quantitative observable to pinpoint this behaviour is the so-called radial pair correlation function g(r), defined as the density of particles at distance r from a focal particle.…”
Section: Pair Radial Correlation Functionmentioning
confidence: 99%
“…However, in real flocks birds seem to move in the center of mass reference frame in a way closer to ballistic than to diffusive, δr 2 ∼ t 1.7 [25,26]. It is therefore possible that the 'right' timescale for enhancing the correlation in natural flocks should be somewhat faster (i.e.…”
mentioning
confidence: 99%